PERNIKAHAN BEDA AGAMA DITINJAU DARI PERSPEKTIF ISLAM DAN HAM - Ahmadi Hasanuddin Dardiri; Marzha Tweedo; Muhammad Irham Roihan (Universitas Islam Indonesia, 2013)
Plurality in religion emerges interfaith marriage as debatable motion in Indonesia in general and Islam specifically. Firstly, there are some different interpretations within fuqaha’ or Islamic scholars concerning this matter influenced by some explanations provided in Holy Qur’an. Secondly, as Indonesia is not a secular state, the legality of marriage is regulated throughout the positive law that religious values are applicable. Thirdly, the notion regarding human rights also challenges the problem solving for couple proposing interfaith marriage. Nevertheless, the juridical and philosophical factors underlay the existence of interfaith marriage have vacuum of law. At any rate, this problem is really imminent to solve as marriage implicates child status either. In conclusion, vacuum of law concerning interfaith marriage shall be answered throughout existing law in Indonesia without setting aside the notion of human rights.